Activation of Nrf2 at Critical Windows of Development Alters Tissue-Specific Protein S-Glutathionylation in the Zebrafish (Danio rerio) Embryo - Emily S. Marques; Emily G. Severance; Paige Arsenault; Sarah M. Zahn; Alicia R. Timme-Laragy (MDPI AG, 2024)
Activation of Nrf2-the master regulator of antioxidative response-at different stages of embryonic development has been shown to result in changes in gene expression, but the tissue-specific and downstream effects of Nrf2 activation during development remain unclear. This work seeks to elucidate the tissue-specific Nrf2 cellular localization and the downstream changes in protein S-glutathionylation during critical windows of zebrafish (Danio rerio) development. Wild-type and mutant zebrafish embryos with a loss-of-function mutation in Nrf2a were treated with two canonical activators, sulforaphane (SFN; 40 µM) or tert-butylhydroquinone (tBHQ; 1 µM), for 6 h at either pharyngula, hatching, or the protruding-mouth stage. Nrf2a protein and S-glutathionylation were visualized in situ using immunohistochemistry. At the hatching stage, Nrf2a protein levels were decreased with SFN, but not tBHQ, exposure. Exposure to both activators, however, decreased downstream S-glutathionylation. Stage- and tissue-specific differences in Nrf2a protein and S-glutathionylation were identified in the pancreatic islet and liver. Protein S-glutathionylation in Nrf2a mutant fish was increased in the liver by both activators, but not the islets, indicating a tissue-specific and Nrf2a-dependent dysregulation. This work demonstrates that critical windows of exposure and Nrf2a activity may influence redox homeostasis and highlights the importance of considering tissue-specific outcomes and sensitivity in developmental redox biology.